2008
DOI: 10.1097/sla.0b013e31816b4399
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Groin Hernia

Abstract: In a large community-based sample of middle-aged men overweight and obesity were associated with a lower risk for groin hernia during an extended follow-up. Obesity, in comparison with normal weight, reduced the risk of groin hernia by 43%. A reduced risk of groin hernia was also noted in heavy smokers. Obviously, hernia may be more easily detected in lean men but a true protective effect cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 21 publications
6
51
1
1
Order By: Relevance
“…In general, IH occurs more frequently among men with low body mass index (BMI), old age, and history of smoking [13, 14]. Anatomically, the internal orifice is penetrated by the spermatic cord and is covered by the transversalis fascia, which act as a supportive structure in preventing development of IH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, IH occurs more frequently among men with low body mass index (BMI), old age, and history of smoking [13, 14]. Anatomically, the internal orifice is penetrated by the spermatic cord and is covered by the transversalis fascia, which act as a supportive structure in preventing development of IH.…”
Section: Discussionmentioning
confidence: 99%
“…Aging may abate tension of the supporting connective tissue surrounding the internal inguinal ring [15]. It may also accelerate deterioration of muscular power of the abdominal muscles [13, 16]. Smoking is a known factor that is related to an increased risk of IH recurrence, since it causes change in the collagen composition by generating tissue hypoxia [14].…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, two studies with results that correlate with ours. One reported a close to significant decrease in hazard ratio (0.82, 95% CI 0.65–1) among current smokers [27], and another reported a significantly decreased hazard ratio among individuals who smoked more than fifteen grams of tobacco each day [28]. …”
Section: Discussionmentioning
confidence: 99%
“…[6][7] Interestingly, data from the Swedish hernia registry showed that the relationship of BMI with post-operative complications after IHR was U-shaped, where complication rates were highest in patients who were underweight or obese. [6] Others have also encountered increased risk for re-admission for obese patients after IHR.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent epidemiologic studies have suggested the opposite: increased weight, along with higher body mass index (BMI), is associated with a decreased risk of requiring an IHR when compared with normal weight individuals. [6, 7][8] Nonetheless, obesity is an established risk factor that increases the risk of recurrence of an IHR. [6] Hence, it is possible that the interaction between body weight and the mechanisms behind the development and recurrence of an IH are different.…”
Section: Introductionmentioning
confidence: 99%